Fabrication and Characterization of Tea Polysaccharide/ZIF-8 Dual-Functionalized Selenium Nanoplatform and Its Application for Synergistic Hepatocarcinoma Therapy - Senhe Qian; Wei Zhong; Zicheng Yang; Yonghai Ruan; Zhou Wang; Hong Li; Guangjun Nie; Rongyu Li (ACS Applied Polymer Materials, 2026)
Abstract Selenium nanoparticles (SeNPs) exhibit promising antitumor activity and drug-loading capacity. However, their high instability and tendency to aggregate often lead to a loss of bioactivity. To address this issue, bioactive tea polysaccharides (TP) were employed as a template to synthesize stable TP@SeNPs (TPS), which were then loaded with the antitumor drug doxorubicin hydrochloride (DOX). Subsequently, the DOX@TP@SeNPs (DTPS) complex was encapsulated within a zeolitic imidazolate framework (ZIF-8), resulting in an antitumor drug delivery system (DOX@TP@SeNPs@ZIF-8, DTPSZ) that combines the targeted release capability of ZIF-8 with the synergistic chemotherapeutic effects of SeNPs and DOX. In this work, the synthesized DTPSZ was characterized, and its anti-HepG2 cell activity, targeting effect, and biosafety were investigated both in vitro and in vivo. The successful synthesis of DTPSZ was confirmed by mapping analysis and spectroscopic characterization. The DTPSZ particles measured approximately 166 nm in diameter with a ζ-potential of +23 mV and exhibited favorable sustained-release characteristics along with good stability in aqueous solution. DTPSZ showed significant efficacy in killing HepG2 cells, inhibiting their migration, and displayed strong HepG2 tumor-targeting capability in mice, leading to pronounced suppression of HepG2 tumor growth. Further analysis revealed that DTPSZ treatment upregulated Caspase-3 expression and reduced the proportion of Ki67-positive cells, demonstrating its capacity to inhibit the proliferation of HepG2 cells and induce their apoptosis. Additionally, DTPSZ demonstrated low cytotoxicity, minimal hemolytic activity, and negligible toxicity to the heart, liver, spleen, lungs, and kidneys. Consequently, DTPSZ holds promise as a potential therapeutic agent for the treatment of hepatocellular carcinoma.